Modern laser technologies in the computer and communication equipment - Kolev, Ivan; Koleva, Elena (Yearbook Telecommunications, 2014)
I. Modern laser technology in computer technologies. II. Modern laser technology in communication equipment. III. Optical computers. Optical information processing. IV. Optical networks. V. Optical solitons. Soliton Optical Communication Systems